2003
DOI: 10.1074/jbc.m208282200
|View full text |Cite
|
Sign up to set email alerts
|

Specificity and Structural Requirements of Phospholipase C-β Stimulation by Rho GTPases Versus G Protein βγ Dimers

Abstract: Phospholipase C-␤ 2 (PLC␤ 2 ) is activated both by heterotrimeric G protein ␣-and ␤␥-subunits and by Rho GTPases. In this study, activated Rho GTPases are shown to stimulate PLC␤ isozymes with the rank order of PLC␤ 2 > PLC␤ 3 > PLC␤ 1 . The sensitivity of PLC␤ isozymes to Rho GTPases was clearly different from that observed for G protein ␤␥ dimers, which decreased in the following order: PLC␤ 3 > PLC␤ 2 > PLC␤ 1 for ␤ 1 ␥ 1/2 and PLC␤ 2 > PLC␤ 1 >>> PLC␤ 3 for ␤ 5 ␥ 2 . Rac1 and Rac2 were found to be more pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
75
0
1

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(86 citation statements)
references
References 58 publications
10
75
0
1
Order By: Relevance
“…For example, this idea also corroborates studies by Illenberger and collaborators using chimera of PLC-β1/PLC-β2 which show that both the PH and the catalytic domain of PLC-β2 are required for Gβγ -activation [78].…”
Section: Gβγ Binding Site(s) In Plc-β2supporting
confidence: 79%
See 2 more Smart Citations
“…For example, this idea also corroborates studies by Illenberger and collaborators using chimera of PLC-β1/PLC-β2 which show that both the PH and the catalytic domain of PLC-β2 are required for Gβγ -activation [78].…”
Section: Gβγ Binding Site(s) In Plc-β2supporting
confidence: 79%
“…Comparing a model structure of PH-β2 with the known structure of PH-δ1 suggests that the β5/β6 loop, which is longer than in PH-δ1, (Figure 3) could act as a regulatory domain for activation by Gβγ [41]. A peptide corresponding to this loop (PHβ [71][72][73][74][75][76][77][78][79][80][81][82][83][84][85][86][87][88] ) activates the enzyme, and this activation is competitive with Gβγ activation. The structure of PLC-β2 reveals that the β5/β6 loop does not belong to the surface that is tightly packed with the EF-hands and the catalytic regions, or to the hydrophobic ridge interacting with Rac2.…”
Section: Role Of the Ph Domain In Plc-δ1 And Plc-β2 Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, recent reports have shown that PLCbs can also be activated by monomeric G proteins, such as Rho GTPases (Illenberger et al, 2003a;Snyder et al, 2003). Rho GTPases bind to the PH domains of PLCb and regulate the activity of each PLCb isozyme independently, and differently, from heterotrimeric G proteins (Illenberger et al, 2003a, b). Importantly, Rho GTPases are most active on the b2 isozyme of PLC, which is not expressed in mouse eggs (Dupont et al, 1996;Illenberger et al, 2003a).…”
Section: Plcbmentioning
confidence: 99%
“…Therefore, the possibility cannot be ruled out that fertilization might activate PLCb isozymes in a non-conventional manner, in which case this antibody would not block the sperm-induced [Ca 2+ ] i oscillations. Interestingly, recent reports have shown that PLCbs can also be activated by monomeric G proteins, such as Rho GTPases (Illenberger et al, 2003a;Snyder et al, 2003). Rho GTPases bind to the PH domains of PLCb and regulate the activity of each PLCb isozyme independently, and differently, from heterotrimeric G proteins (Illenberger et al, 2003a, b).…”
Section: Plcbmentioning
confidence: 99%